Diagnostic evaluation and surgical management of recurrent hydatid cysts in an endemic region - Yildirim, Mehmet (Radiology and oncology (Ljubljana), 2009)
Background. Xanthogranulomatous cholecystitis (XGC) is a rare, benign, chronicinflammatory disease of the gallbladder. Its importance lies in the fact that imaging studies and intraoperative appearance that may be confused with tumour of the gallbladder. This study aimed to evaluate pre-and intraoperative findings of XGC and to remind it in difficult cholecystectomy patients. Patients and methods. The clinical data of 24 patients with XGC overa period of 7 years were analyzed retrospectively (mean age, 53 years (32-68) M/F ratio 1:1.4). Results. The clinical symptoms were abdominal pain, nausea and jaundice in 79%, 62% and 12% of the patients. Preoperative ultrasonography for 24 patients revealed gallstone (95.8%) and bile sludge (8%). Pericholecystic fluid, polyp and tumour of the gallbladder was present in 20%, 4% and 4% of the patients. The gallbladder was thickened (>3mm) in 10 patients. On computed tomography, all patients showed abnormal findings. The intraoperative findings were as follows: gallstones (100%), chronic cholecystitis (54%), hydropic gallbladder, emphysematous gallbladder, adhesions of the gallbladder to adjacent organs and tumoural mass of gallbladder. Conclusions. XGC is difficult to diagnose pre-or intraoperativelyand remains a challenge in medical practice. The definitive diagnosis depends on the histopathologic examination.
Keywords: diagnostika; ehinokokoza; hidatidne ciste; kirurško zdravljenje; zoonoze